On freedom, lack of information and the preference for easy choices - Ritxar Arlegi; Dinko Dimitrov (Bielefeld University, Institute of Mathematical Economics (IMW), 2005)
This paper is devoted to the study of opportunity sets comparisons when the sets may contain options whose characteristics are not completely known. We propose a suitable environment in which this problem can be approached, and provide axiomatic characterizations of several rules for ranking sets in such a context.
urn:nbn:de:hbz:361-6657
Keywords: D81; 330; Freedom of choice; Lack of information; Extended opportunity sets; Easy choices; Entscheidung bei Unsicherheit; Theorie